Analisis Penerapan Restorative Justice dalam Kasus Tindak Pidana Ringan Sebagai Upaya Mengurangi Over Kapasitas di Lembaga Pemasyarakatan - Anwar Sulaiman; Asmak ul Hosnah (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2022)
In the application of criminal sanctions against criminal acts of theft in Indonesia, there is currently a paradigm shift from which initially still adheres to a system of retaliation against perpetrators of criminal acts into restoration to its original state, and not retaliation. This is expected to be one of the solutions to the problem of over capacity in Correctional Institutions. This type of research in legal writing is normative legal research with the nature of descriptive analytical research and a statutory approach, while the data collection technique uses library research and field research and data processing is carried out qualitatively. In the implementation of restorative justice there are several obstacles both at the investigator level and at the court level, including refusal from the parties involved to meet, the perpetrator does not want to pay the compensation proposed by the victim, the judge has not fully implemented restorative justice, there is no law that regulates explicitly regarding restorative justice and its application is only limited to minor crimes and imprisonment with a threat of five years in prison. Most law enforcers (police, prosecutors and judges) still have the mindset that crimes must end retributively (punishment) or still prioritize prison sentences besides that the level of public legal awareness is still low and one of the parties violates the agreement.